Interpreting the evidence for New Keynesian models of inflation dynamics - Ragnar Nymoen; Anders Rygh Swensen; Eivind Tveter (University of Oslo, Department of Economics, 2011)
We present a framework for interpretation of the empirical results of New Keynesian models of inflation dynamics. Both the rational expectations solution of the structural New Keynesian Phillips curve, NKPC, and the reduced form VAR analysis of the multivariate time series properties give insight about the joint implications of the evidence in the NKPC literature. For example, we show that the unit-root form of non-stationary may be implied for inflation even though the econometric model initally assumed stationarity. We point out and suggest a correction to an error in the literature regarding the existence or not of a rational expectations solution in the case of homogeneity and forward-dominance.
Keywords: B41; C22; E31; E52; 330; New Keynesian Phillips Curve; forward-looking price setting; rational expectations; VAR model; New-Keynesian Phillips Curve; VAR-Modell; Rationale Erwartung; Zeitreihenanalyse; Theorie